Reverse smokers’s and changes in oral mucosa. Department of Sucre, Colombia (2008)
ABSTRACT: Objectives: This work is intended to establish the prevalence of reverse smokers at the villages of Hato Nuevo, San Francisco and Cayo de Palma, Department of Sucre, Colombia, characterizing their socio-culture conditions, clinical and histological changes in the oral mucosa. Design of study: A descriptive study was done through a home to home inquiry to select the people with inclusion criteria for a posterior clinical test and a biopsy of the affected oral mucosa. Results and conclusions: Reverse smokers’s prevalence was from 15%, mainly women (p<0.001) with an age average of 59.3 years. The lesions were classified clinically in mild, moderate and severe changes. Tongue moderate lesions presented the higher frequency (80%), followed by severe lesions on the palate (74%). Oral cancer prevalence was 10.8% in the San Francisco village and 18.2% in Cayo de Palma village, no new cases were reported in Hato Nuevo village. This was the highest prevalence reported in comparison with other studies with similar populations. The clinical and histological findings agree with the reported in literature, no relation was found between the degree of clinical severity and the dysplasia itself. Cases of oral submucous fibrosis-like lesions were found, which had never been reported in Latin America. Further studies are required in order to decrease the morbidity for this habit and to identify other related risk factors.